ANALISIS PENDAPATAN DAN TINGKAT KESEJAHTERAAN RUMAH TANGGA PETANI JAGUNG DI KELURAHAN SIDOSARI, KABUPATEN LAMPUNG SELATAN - Larasati, Tia; Murniati, Ktut; Adawiyah, Rabiatul (Lampung University, 2025)
This research aims to assess the income level and welfare status of corn farmers in Sidosari Village, because the level of income and welfare of corn farmers in several regions in Indonesia is lower than the indicator sets by the word bank. Various factors underlying this situation, both from internal and external of agriculture system, such as pests and diseases, and lack of public awareness regarding the use of empty lands. The study was carried out in Sidosari Village, Natar District, South Lampung Regency, which was intentionally selected (purposively) due to its status as a main corn production area in the region. The data utilized include both primary data gathered through direct observation and secondary data obtained from relevant agencies. A total of 46 farming households were chosen as respondents through simple random sampling. The research employed a quantitative descriptive approach, involving income analysis and welfare evaluation based on Sajogyo's (1997) theory. Findings reveal that the average household income for corn farmers amounts to IDR 41,975,181.08 annually, with the majority of income 81.07 percent comes from on-farm activities, specifically 71.98 percent from corn farming with an average land area of 1,07 ha and 9.09 percent from rice farming with an average rice field area of 0.16 ha. Based on Sajogyo (1997) criteria, corn farmers households per capita in Sidosari Subdistrict fell into the near poor living category at 6.52 percent, the criteria far-fairly prosperous life is 84.72 percent and the criteria for a decent living is 8.70 percent. Keywords: corn farmer, income, welfare